Translating Culture Specific Items: A Study of Translation Strategies in a Guidebook - Ikawati, Listiana (Foreign Language Instruction Probe, 2022)
Culture Specific Items (CSIs) have become challenges for translators in transferring one language to another. This research aimed at investigating the types of CSIs and the translation strategies applied by the translation in the translation of Wonogiri guidebook. A qualitative method was used to collect and analyze the data from the guidebook. The study shows that the CSIs found in the guidebook can be classified into 6 main categories: (1) toponyms, (2) anthroponyms, (3) legal systems, (4) food and drink, (5) religious celebration, and (6) local institution. Toponyms are the most categories found (62.5%). The toponyms were categorized further into 7 categories including 1 additional category, given names of plants. Additionally, the study also reveals that the translator mainly used 2 categories of translation strategy, namely preservation and addition. Both strategies indicate that the translator applies foreignization strategies. It implies that the translator attempts to maintain the originality and uniqueness of the CSIs in the target text. It suggests that translators’ decisions to apply certain translation strategies in translating CSIs reflect their discretion regarding their perception of CSIs and consideration on the translation quality.